A review of Antillocladius S ther, 1981; Compterosmittia S ther, 1981 and Litocladius new genus (Chironomidae, Orthocladiinae) - Mendes, Humberto F.; Andersen, Trond; Sæther, Ole A. (Zootaxa, 2004)
A parsimony analysis of recently collected species sharing several features such as scalpellate acrostichals, often setae apically on the wing membrane and often strongly extended costa, together with 38 genera show that the collected species can be assigned to Antillocladius S ther, 1981, Compterosmittia S ther, 1981, and one new genus, Litocladius. Nine new species of Antillocladius are described and figured as male imagines: A. calakmulensis, A. herradurus and A. zempoalensis from Mexico; A. venequatoriensis from Ecuador and Venezuela; A. ubatuba from Brazil and Venezuela; and A. biota, A. folius, A. musci, and A. sooretama from Brazil. The female of A. musci, the pupae of A. antecalvus S ther, A. folius, and A. musci, and the larvae of A. folius and A. musci are also described and figured. New records of A. antecalvus S ther from Brazil and Venezuela; of A. arcuatus S ther from Brazil, Mexico and Venezuela; A. pluspilalus S ther from Ecuador and Mexico and of A. zhengi Wang and S ther from Thailand are given. The genus Antillocladius S ther, 1981, originally described from the British West Indies, now includes 15 species from North, Central and South America, Russia, China and Thailand. Keys to all known males, females, pupae and larvae are given. Four new species of Compterosmittia are described and figured as male imagines: C. aberrans from Costa Rica; C. croizati from Brazil and Venezuela; C. pittieri from Venezuela; and C. berui from Brazil. The genus Compterosmittia S ther, 1981, originally described from the British West Indies, now includes 8 to 10 species from North, Central and South America, Australia, Oceania and Southeast Asia. A key to male imagines is given. The new genus, Litocladius, includes a single species, L. mateusi, described as male, female and pupa. The immatures of all three genera are terrestrial or associated with phytotelmata, and notes on their biology and larval habitats are included.